2016
DOI: 10.1080/1828051x.2016.1249967
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation ofMoringa oleiferaleaf in laying hens: effects on laying performance, egg quality, plasma biochemistry and organ histopathological indices

Abstract: This experiment was conducted to evaluate the effects of supplementary Moringa oleifera leaf (MOL) on performance, egg quality, plasma parameters and organ histopathological indices of layers. A total of 360 27-week-old Hy-Line Grey commercial layers were randomly allotted to four groups. Each group consisted of six replicates with 15 birds and 3 birds were placed in one cage. The control group was fed a corn-soybean meal based diet and the experimental groups were fed on control diet supplemented with 5%, 10%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
2
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 21 publications
7
56
2
6
Order By: Relevance
“…ALT, albumin, total protein, globulin, and the albumin/ globulin ratio (A/G) were not affected due to any dietary treatment. Laying hens in the ML group had a lower concentration of albumen (ALB) and urea (UA) than those in the control group (p < 0.05) [36]. AST decreased with M. oleifera supplementation.…”
Section: Effect Of M Oleifera On Blood Biochemical Indicesmentioning
confidence: 96%
See 1 more Smart Citation
“…ALT, albumin, total protein, globulin, and the albumin/ globulin ratio (A/G) were not affected due to any dietary treatment. Laying hens in the ML group had a lower concentration of albumen (ALB) and urea (UA) than those in the control group (p < 0.05) [36]. AST decreased with M. oleifera supplementation.…”
Section: Effect Of M Oleifera On Blood Biochemical Indicesmentioning
confidence: 96%
“…Whereas, egg index, shell percent, yolk percent, albumen percent, Haugh unit, and yolk index were not affected by the dietary supplementation. There was no difference in Haugh units, eggshell strength, or egg shape index among the groups (p > 0.05) in response to dietary M. oleifera leaves [34][35][36]. Ebenebe et al [37] reported that adding MOL had no effect on egg shape index that's correlated with the strength of an eggshell and the grade of eggs.…”
Section: Effect Of M Oleifera On Egg Qualitymentioning
confidence: 99%
“…Significant decrease in GPT and GOT with Moringa oleifera supplementation reported by Annongu et al (2013) which may attribute to Moringa oleifera have relative hepatic architectural improvements and induced liver damage (Bahr and Farouk, 2016). The results of liver enzymes disagreement with (Lu et al, 2016) who reported that fed layers in 15% Moringa oleifera meal had higher GOT activity. Their dissimilarity results may be due to feeding so high Moringa oleifera meal level nevertheless, they found no significant effects of supplementary Moringa oleifera leaf up to 10% on GOT and GPT activity.…”
Section: Plasma Componentsmentioning
confidence: 94%
“…Feeding layers Moringa oleifera leaf 10% and 15% supplementation had higher malondialdehyde content than those in control group (p<0.05) moreover supplementary Moringa oleifera leaf increased the activity of glutathione peroxidase (p<0.05) (Lu et al, 2016). Jalo et al (2016) reported that supplementing laying chickens' diet with M. oleifera seed meal at (0.04, 0.08, 0.12 and 0.16%) has no significant effect on feed intake whereas egg weight improved significantly at 0.16%.…”
Section: Introductionmentioning
confidence: 92%
“…oleifera is very useful as a dietary supplement for animals, because the leaves are a highly nutritious protein source and include other essential nutrients as well (Babiker, Juhaimia, Ghafoora, & Abdoun, 2017;Yusuf, Mlambo, & Iposu, 2018). The leaves of M. oleifera contain fairly high quantities of essential amino acids (Lu, Wang, Zhang, Wu, & Qi, 2016) and are rich with vitamin A, B, C, K and E and pro-vitamin A as beta-carotene in addition to minerals such as Ca, P, Zn, Fe, Mg, K, Cu, Na, Mn (Chelliah, Ramakrishnan, & Antony, 2017;Leone et al, 2015). Moreover, M. oleifera was reported to be an excellent source of important bioactive compounds as its leaves are rich in total phenols and saponins and can serve as a novel plant to develop anticoccidial drugs and new therapeutic compounds (Alabi, Malik, & Ng'ambi, Obaje, & Ojo, 2017).…”
mentioning
confidence: 99%